Lightweight sound-absorbing mute cotton and preparation method thereof
Through the gradient structure design, the lightweight sound-absorbing silent cotton solves the problems of low-frequency sound wave absorption efficiency and insufficient mechanical strength of automotive sound-absorbing materials, and achieves wide-frequency sound absorption and environmental adaptability, which is suitable for noise optimization of electric vehicles.
Patent Information
- Application Number
- CN202510740482.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2025-08-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing automotive sound-absorbing materials have low low-frequency sound absorption efficiency, insufficient mechanical strength and poor environmental adaptability, especially in electric vehicles stroke noise, road noise and high-frequency motor noise, which are more prominent, and traditional materials are difficult to meet the needs of lightweight and high performance.
The gradient structure design is adopted to form a bionic gradient structure by regulating the pore size, fiber distribution and filler type. The bottom layer is PU/carbon nanotube-containing composite large microspheres and TEMPO oxidized cellulose nanofibers, the middle layer is PU/graphene composite medium microspheres and medium nanofibers, and the upper layer is pure PU microspheres and lignin carbon fibers. Combined with epoxy soybean oil as a damper, the absorption of sound waves in different frequency bands is optimized.
It improves sound absorption efficiency, enhances the compressive strength and environmental adaptability of the material, can effectively reduce wide-frequency noise, especially low-frequency sound waves, reduces sound wave reflection and structural deformation, and adapts to the humid and heat and salt spray environment of the car.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound insulation materials, and in particular to a lightweight sound-absorbing and silent sponge and a preparation method thereof. Background Art
[0002] As the automotive industry moves toward electrification and intelligent driving, vehicle NVH (Noise, Vibration, and Harshness) performance requirements are increasing. Noise in traditional internal combustion engine vehicles primarily stems from the engine, exhaust system, and mechanical vibration. However, the absence of an engine in electric vehicles increases the prevalence of wind noise, road noise, and high-frequency motor noise. Therefore, developing high-performance, lightweight sound-absorbing materials that effectively reduce broadband noise (especially low-frequency noise) has become a key technical challenge in optimizing automotive NVH.
[0003] The commonly used sound-absorbing materials in automobiles at present mainly include: (1) porous foam materials (such as polyurethane foam, melamine foam): advantages: light weight, easy to process, good sound absorption effect for medium and high frequencies (such as >1000Hz); disadvantages: poor sound absorption performance at low frequencies (<1000Hz), low mechanical strength, and easy to collapse after long-term use. (2) fiber materials (such as glass fiber, PET fiber): advantages: better low-frequency sound absorption than foam materials; disadvantages: high density, not conducive to lightweight, and easy fiber shedding, which may endanger health. The technical problems that need to be solved urgently are: (1) low low-frequency sound absorption efficiency: low-frequency sound waves (such as 500-1000Hz) have long wavelengths, and traditional porous materials are difficult to effectively absorb through viscous dissipation. They need to rely on resonant structures or high surface density materials, but this will increase weight. (2) contradiction between mechanical properties and lightweight: high sound absorption materials usually require high porosity, but this will sacrifice strength, resulting in easy deformation and failure under vehicle vibration environment. (3) Insufficient environmental adaptability: The automotive environment needs to withstand corrosive conditions such as humidity, heat, and salt spray. However, ordinary sound-absorbing materials (such as CNT-enhanced foam) are easily oxidized under humidity and heat, resulting in performance degradation. Therefore, to address the above issues, it is urgent to develop a lightweight, high-strength, broadband sound-absorbing mute sponge. Summary of the Invention
[0004] Technical problem to be solved: In response to the above technical problems, the purpose of the present invention is to provide a lightweight sound-absorbing and silent cotton and a preparation method thereof, which adopts a gradient structure design and realizes a gradual change of acoustic impedance by regulating the pore size, fiber distribution and filler type, reduces sound wave reflection and improves sound absorption efficiency. Specifically, the bottom layer is composed of PU / carbon nanotube composite large microspheres and low-content TEMPO oxidized cellulose nanofibers to form a larger pore size (micron level), which dissipates high-frequency sound waves through viscous resistance, and TEMPO oxidized cellulose nanofibers enhance the rigidity of the skeleton and reduce the sound energy reflection caused by structural vibration; the middle layer is composed of PU / graphene composite medium microspheres and medium nanofibers to form a transitional pore size, optimize the medium-frequency resonance, and the high specific surface area of graphene enhances sound wave scattering and extends the propagation path; the upper layer is composed of pure PU small microspheres and lignin carbon fibers, combined with high-content nanofibers to form a denser small pore / fiber network, which dissipates low-frequency sound waves through scattering and multiple reflections. At the same time, epoxidized soybean oil can be used as a damping agent to further consume low-frequency vibration energy.
[0005] Technical solution: A lightweight sound-absorbing and silent cotton, which has a bionic gradient structure and is divided into three layers. The bottom layer dissipates high-frequency sound waves (>3000Hz), the middle layer optimizes medium-frequency resonance (1000-3000Hz), and the upper layer enhances low-frequency sound wave scattering (500-1000Hz).
[0006] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% TEMPO oxidized cellulose nanofibers, 18-20 wt.% PU / carbon nanotube composite microspheres, 35 wt.% aqueous polyurethane emulsion, 1 wt.% sodium alginate, 0.1 wt.% silane coupling agent KH550, and the remainder water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers, 15-18 wt.% of PU / graphene composite microspheres, 35 wt.% of aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of silane coupling agent KH550, and the remainder of water are mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% TEMPO oxidized cellulose nanofibers, 10-12 wt.% pure PU microspheres, 1-2 wt.% lignin carbon fibers, 1 wt.% epoxidized soybean oil, 35 wt.% aqueous polyurethane emulsion, 0.1 wt.% silane coupling agent KH550, and the remainder water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60 °C, add 0.1 wt% ascorbic acid, hold for 2 h, and apply 0.5% pre-strain to the material; Step 9: Photothermal curing: UV curing after near-infrared treatment; Step 10: Heat press and shape.
[0007] Furthermore, in step 1, the diameter of the TEMPO oxidized cellulose nanofibers is 20-50 nm, and the particle size of the PU / carbon nanotube composite macromicrospheres is 30-80 μm.
[0008] Furthermore, the preparation method of the PU / carbon nanotube composite large microspheres in step 1 is as follows: take 20wt.% of a carboxylated CNT dispersion with a concentration of 1wt.% and slowly add it to 60wt.% of a PU emulsion with a solid content of 30wt.%, stir magnetically at 500rpm for 30min, homogenize under high pressure at 50MPa, add 2wt.% hydroxyethyl cellulose and 18wt.% deionized water and stir, spray dry to form, and cure in an oven at 80°C for 2h to obtain the product.
[0009] Furthermore, the spray drying molding conditions are: inlet air temperature: 180°C, outlet air temperature: 80°C, atomization pressure: 0.3 MPa, and feed rate: 5 mL / min.
[0010] Furthermore, in step 2, the diameter of the TEMPO-oxidized cellulose nanofibers is 20-50 nm, and the particle size of the microspheres in the PU / graphene composite is 15-30 μm.
[0011] Furthermore, the preparation method of the PU / graphene composite microspheres in step 2 is as follows: 50 wt.% polyurethane prepolymer (NCO: 6-8%), 30 wt.% acetone and 0.1 wt.% dibutyltin dilaurate are mixed to obtain an oil phase; 15 wt.% GO dispersion (GO content is 0.5 wt.%) and 4.9 wt.% emulsifier (Tween-80 / sodium dodecyl sulfate = 2:1) are mixed to obtain an aqueous phase; the oil phase and the aqueous phase are mixed at 50°C, sheared and emulsified at 10,000 rpm for 10 minutes; the homogenization pressure is 20 MPa and the cycle is repeated three times to obtain a W / O emulsion; ethylenediamine (0.5 wt.% in the aqueous phase) is added, and the reaction is carried out at 60°C for 2 hours; the acetone is slowly evaporated at 40°C for 6 hours to form dense microspheres, which are then immersed in 1 wt.% ascorbic acid at 60°C for 12 hours, and PU / graphene composite microspheres with a size of 15-30 μm are obtained by screening.
[0012] Furthermore, in step 3, the diameter of the TEMPO oxidized cellulose nanofibers is 20-50 nm, the particle size of the pure PU microspheres is 5-10 μm, and the particle size of the lignin carbon fibers is 1-2 μm.
[0013] Furthermore, the preparation method of pure PU microspheres in step 3 is as follows: 10 g of polyurethane prepolymer and 50 mL of dichloromethane are mixed to obtain an oil phase; 200 mL of a 2-3 wt% polyvinyl alcohol aqueous solution and 0.2 g of sodium lauryl sulfate are mixed to obtain an aqueous phase; the oil phase is poured into the aqueous phase, and high-speed shear emulsification is performed at 25° C. and 17,000 rpm for 5 minutes to form an O / W emulsion; magnetic stirring is performed at 300 rpm for 6 hours to form microspheres, which are centrifuged and washed at 5,000 rpm and freeze-dried.
[0014] Furthermore, the 0.5% pre-strain is: fixing the material on a stretching machine, stretching it to a strain of 0.5% at a constant rate of 1 mm / min, maintaining it for 8-9 minutes, and then releasing it.
[0015] Furthermore, the near infrared treatment conditions in step 9 are 808 nm, 1 W / cm 2 , 30s; UV curing conditions are 365nm, 600-800mJ / cm 2 .
[0016] Furthermore, the hot pressing and shaping conditions in step 10 are 0.1 MPa, 60° C., and 5 min. Beneficial effects
[0017] The present invention adopts a gradient structure design, and achieves gradual change of acoustic impedance by regulating the pore size, fiber distribution and filler type, thereby reducing sound wave reflection and improving sound absorption efficiency. Specifically, the bottom layer is composed of large PU / carbon nanotube composite microspheres and low-content TEMPO oxidized cellulose nanofibers, forming a larger pore size (micrometer level), which dissipates high-frequency sound waves through viscous resistance, and TEMPO oxidized cellulose nanofibers enhance skeleton rigidity and reduce sound energy reflection caused by structural vibration; the middle layer is composed of medium PU / graphene composite microspheres and medium nanofibers, forming a transitional pore size and optimizing medium-frequency resonance. The high specific surface area of graphene enhances sound wave scattering and extends the propagation path; the upper layer is composed of small pure PU microspheres and lignin carbon fibers, combined with high-content nanofibers, to form a denser small pore / fiber network, which dissipates low-frequency sound waves through scattering and multiple reflections. At the same time, epoxidized soybean oil can be used as a damping agent to further consume low-frequency vibration energy.
[0018] The present invention forms a longitudinal gradient pore size from the bottom layer (50μm) to the upper layer (5μm) through unidirectional freezing (-50°C). The gradient pore size allows sound waves to gradually transition from the large pores to the small pores after entering, reducing reflections caused by sudden changes in acoustic impedance (compared with the uniform pore size of Example 4, the sound absorption coefficient is reduced by 10%), further supporting the three-layer targeted dissipation mechanism of sound waves in different frequency bands.
[0019] The CNT network in the bottom layer of the present invention is homogenously dispersed in the PU matrix through high pressure, forming a 3D conductive-mechanical network, which improves the compressive strength (Example 8: 1.12 MPa, Comparative Example 1 without CNT: 0.75 MPa). The high modulus of CNTs inhibits the slippage of PU molecular chains and reduces plastic deformation.
[0020] The sheet structure of the middle-layer graphene of the present invention can delay material fracture through crack deflection and stress transmission.
[0021] In the present invention, TEMPO oxidized cellulose nanofibers (20-50 nm) penetrate the three-layer interface and form physical cross-linking points through hydrogen bonds with PU via hydroxyl groups, significantly improving the interlayer bonding strength.
[0022] In the present invention, the macroporous layer (bottom layer) absorbs compressive stress, and the microporous layer (upper layer) provides support to prevent structural collapse (the compressive strength of Example 8 is 24% higher than that of Comparative Example 4).
[0023] The present invention introduces graphene oxide quantum dots and vacuum impregnation to uniformly penetrate the inner walls of the pores to form a three-dimensional conductive network. Prestrain (0.5%) optimizes the distribution of quantum dots and reduces contact resistance (Example 8 has a sensitivity of 8.7% / kPavs. Comparative Example 7 has a 30% increase in hysteresis without prestrain).
[0024] When the material of the present invention is subjected to pressure, the pore deformation causes the GQD spacing to change, triggering a tunneling resistance effect, and the synergistic effect of graphene / CNT improves signal stability.
[0025] The hydrophobicity and chemical inertness of the lignin carbon fibers in the present invention can block Cl - penetration (after salt spray testing, the strength of Example 8 dropped by only 5%, while the CNT oxidation of Comparative Example 2 resulted in a +25% fluctuation).
[0026] In the present invention, the long-chain alkanes of the epoxidized soybean oil wrap the PU molecules, thereby reducing the diffusion rate of water molecules and forming hydrophobic protection. After wet-heat aging, the sound absorption coefficient only decreases by 2%. DETAILED DESCRIPTION
[0027] The present invention provides a lightweight sound-absorbing and silent foam and a method for preparing the same. To make the objectives, technical solutions, and effects of the present invention more clear and explicit, the present invention will be further described in detail with reference to the following examples. It should be understood that the specific examples described herein are intended only to illustrate the present invention and are not intended to limit the present invention. Example
[0028] The preparation method of PU / carbon nanotube composite large microspheres is as follows: 20g of a carboxylated CNT dispersion with a concentration of 1wt.% is slowly added to 60g of a PU emulsion with a solid content of 30wt.% (brand: Covestro Dispercoll U 54), magnetically stirred at 500rpm for 30min, homogenized at 50MPa high pressure, 2g of hydroxyethyl cellulose and 18g of deionized water are added and stirred, spray dried to form, inlet air temperature: 180°C, outlet air temperature: 80°C, atomization pressure: 0.3MPa, feed rate: 5mL / min; cured in an 80°C oven for 2h to obtain PU / carbon nanotube composite large microspheres with a particle size of 30-80μm. Example
[0029] The preparation method of PU / graphene composite mesospheres is as follows: 50g of polyurethane prepolymer (NCO: 7.8%), 30g of acetone and 0.1g of dibutyltin dilaurate are mixed to obtain an oil phase; 15g of GO dispersion (GO content is 0.5wt.%) and 4.9g of emulsifier (Tween-80 / sodium dodecyl sulfate = 2:1) are mixed to obtain an aqueous phase; the oil phase and the aqueous phase are mixed at 50°C and shear emulsified at 10,000rpm for 10min; the homogenization pressure is 20MPa and the cycle is repeated three times to obtain a W / O emulsion; 0.0995g of ethylenediamine is added and the mixture is reacted at 60°C for 2h; the acetone is slowly evaporated at 40°C for 6h to form dense microspheres, which are then immersed in 1wt.% ascorbic acid at 60°C for 12h to obtain PU / graphene composite mesospheres with a size of 15-30μm. Example
[0030] The preparation method of pure PU microspheres is as follows: take 10g of polyurethane prepolymer (NCO: 7.8%) and mix it with 50mL of dichloromethane to obtain an oil phase; take 200mL of polyvinyl alcohol aqueous solution with a concentration of 2-3wt% and mix it with 0.2g of sodium lauryl sulfate to obtain an aqueous phase; pour the oil phase into the aqueous phase, and emulsify it at high speed shear at 25°C and 17,000rpm for 5min to form an O / W emulsion; magnetic stirring is carried out at 300rpm for 6h to form microspheres, which are centrifuged and washed at 5,000rpm and freeze-dried to obtain pure PU microspheres with a particle size of 5-10μm. Example
[0031] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 18 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0032] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0033] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 20 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0034] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 15 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0035] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 18 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0036] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 10 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product. Example
[0037] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 12 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0038] The difference between this embodiment and embodiment 5 is that PU / carbon nanotube composite large microspheres are not used.
[0039] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 3: Pre-cool the bottom of the mold to -30°C and use a two-channel injection system to simultaneously co-inject the two layers: Bottom slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 2 mm; Step 4: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 5: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a two-layer gradient structure material; Step 6: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 7: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 8: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0040] The difference between this embodiment and embodiment 5 is that PU / graphene composite microspheres are not used.
[0041] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 3: Pre-cool the bottom of the mold to -30°C and use a two-channel injection system to simultaneously co-inject the two layers: Bottom slurry injection flow rate: 0.1 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 2 mm; Step 4: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 5: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a two-layer gradient structure material; Step 6: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 7: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 8: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 9: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0042] The difference between this embodiment and embodiment 5 is that pure PU microspheres are not used.
[0043] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a two-channel injection system to simultaneously co-inject the two layers: Bottom slurry injection flow rate: 0.1 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a two-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0044] The difference between this embodiment and embodiment 5 is that the one-way freezing is modified to conventional freeze-drying.
[0045] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Conventional freezing: After injection, let it stand for 1 minute, then place the entire mold in a -50°C environment and freeze for 20 minutes to form a uniform pore size (20±5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0046] The difference between this embodiment and embodiment 5 is that only the middle layer slurry is used.
[0047] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a slurry; Step 2: Precool the bottom of the mold to -30°C and inject the slurry: slurry injection rate: 0.15 mL / s, injection height: 4 mm; Step 3: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 4: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a gradient structure material; Step 5: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 6: Heat to 60°C, add 0.1 wt% ascorbic acid, hold for 2 h, fix the material on a stretching machine, stretch at a constant rate of 1 mm / min to a strain of 0.5%, hold for 8 min, and then release; Step 7: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 8: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0048] The difference between this embodiment and embodiment 5 is that there is no GQD sensing network.
[0049] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 8: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0050] The difference between this embodiment and embodiment 5 is that there is no pre-strain treatment.
[0051] A method for preparing a lightweight sound-absorbing and silent sponge comprises the following steps: Step 1: 3 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 19 wt.% of the PU / carbon nanotube composite macromicrospheres prepared in Example 1, 35 wt.% of an aqueous polyurethane emulsion, 1 wt.% of sodium alginate, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers with a diameter of 20-50 nm, 17 wt.% of the PU / graphene composite microspheres prepared in Example 2, 35 wt.% of an aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of a silane coupling agent KH550, and the remainder of water were mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% of TEMPO-oxidized cellulose nanofibers with a diameter of 20-50 nm, 11 wt.% of pure PU microspheres prepared in Example 3, 2 wt.% of lignin carbon fibers with a particle size of 1-2 μm, 1 wt.% of epoxy soybean oil, 35 wt.% of aqueous polyurethane emulsion, 0.1 wt.% of silane coupling agent KH550, and the balance water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: Unidirectional freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold plate, open the top, and freeze for 20 minutes to form a longitudinal gradient pore size (bottom layer 50μm → upper layer 5μm); Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60°C, add 0.1 wt% ascorbic acid, and maintain for 2 h; Step 9: Photothermal curing: 808nm, 1W / cm 2 After 30s of near-infrared treatment, the UV curing conditions were 365nm and 700mJ / cm 2 ; Step 10: hot press at 0.1 MPa and 60°C for 5 minutes to obtain the product.
[0052] Performance testing: Compressive strength: according to ASTM D1621 Standard Test Method for Compression Properties of Rigid Foam Plastics; Interlayer peeling strength: According to GB / T 8808-1988 "Peeling test method for soft composite plastic materials" The results are shown in Table 1 below: Table 1 Mechanical properties <![CDATA[Density (g / cm 3 )]]> Compressive strength (MPa) Interlayer peel strength (N / cm) Example 4 0.18±0.02 1.05±0.10 12.0±1.0 Example 5 0.17±0.02 1.10±0.10 12.5±1.0 Example 6 0.19±0.02 1.00±0.10 11.8±1.2 Example 7 0.18±0.02 1.02±0.09 11.9±1.1 Example 8 0.17±0.02 1.12±0.11 12.8±1.0 Example 9 0.18±0.02 1.08±0.10 12.2±1.0 Example 10 0.19±0.02 1.05±0.10 12.5±1.0 Comparative Example 1 0.21±0.03 0.75±0.08 8.5±1.0 Comparative Example 2 0.20±0.02 0.85±0.09 9.2±1.1 Comparative Example 3 0.22±0.02 0.80±0.09 8.8±1.0 Comparative Example 4 0.23±0.02 0.90±0.10 10.5±1.0 Comparative Example 5 0.25±0.03 0.70±0.08 - Comparative Example 6 0.18±0.02 1.08±0.10 12.3±1.0 Comparative Example 7 0.17±0.02 1.05±0.10 11.9±1.0 As can be seen in Table 1 above, the compressive strength of Example 8 is 1.12 MPa, while the compressive strength of Comparative Example 4 is 0.90 MPa. This demonstrates that the gradient pore size (50→5 μm) formed by unidirectional freezing is more resistant to collapse than the uniform pore size (20±5 μm), primarily because the large pore layer absorbs energy while the small pore layer provides support. The interlayer peel strength of Example 5 is 12.5 N / cm, 42% higher than the 8.8 N / cm of Comparative Example 3. This is primarily due to the "rivet effect" formed by the TEMPO-oxidized cellulose nanofibers in the three-layer slurry penetrating the interface. Comparative Example 1 does not use PU / carbon nanotube composite large microspheres, and the compressive strength is reduced by 32%, primarily because the CNT network can enhance the rigidity of the PU. Comparative Example 3 does not use pure PU small microspheres, resulting in a decrease in peel strength, demonstrating that it can improve interlayer toughness.
[0053] Sound absorption coefficient test: According to the standard: ISO 10534-2:2023 Acoustic impedance tube acoustic characteristics test Response sensitivity: Pressure-resistance test system: pressure source: pneumatic loading (0-1kPa, accuracy ±1Pa), resistance measurement: four-probe method; Sensitivity calculation: ΔR / R0×100% / kPa (R0 is the initial resistance) Table 2 Sound absorption coefficient (500-1000Hz) Average sound absorption coefficient (1-5kHz) Resistance response sensitivity (% / kPa) Thermal conductivity (W / m·K) Example 4 0.62±0.04 0.81±0.03 8.2±0.6 0.035±0.003 Example 5 0.65±0.03 0.83±0.02 8.5±0.5 0.033±0.002 Example 6 0.60±0.05 0.80±0.04 8.0±0.7 0.037±0.003 Example 7 0.58±0.04 0.79±0.03 8.1±0.6 0.036±0.002 Example 8 0.68±0.03 0.84±0.02 8.7±0.5 0.032±0.002 Example 9 0.63±0.04 0.81±0.03 8.3±0.6 0.034±0.003 Example 10 0.64±0.03 0.82±0.03 8.4±0.5 0.035±0.002 Comparative Example 1 0.45±0.06 0.65±0.05 6.0±0.8 0.042±0.004 Comparative Example 2 0.50±0.05 0.70±0.04 5.8±0.7 0.040±0.003 Comparative Example 3 0.48±0.06 0.68±0.05 6.2±0.6 0.043±0.004 Comparative Example 4 0.55±0.04 0.72±0.03 7.2±0.6 0.038±0.003 Comparative Example 5 0.35±0.07 0.58±0.05 - 0.045±0.004 Comparative Example 6 0.61±0.04 0.82±0.03 - 0.050±0.005 Comparative Example 7 0.60±0.04 0.81±0.03 5.5±0.5 0.034±0.003 As shown in Table 2 above, Example 8 exhibits a 500-1000 Hz sound absorption coefficient of 0.68, significantly higher than Comparative Examples 1-5 (≤0.55). This is primarily due to the dense pore structure formed by the upper layer of pure PU microspheres, which synergistically enhance low-frequency sound scattering with the lignin carbon fibers. Their elastic deformation, combined with the epoxy soybean oil, enhances damping energy dissipation. Interfacial hydrogen bonding maintains the integrity of the gradient structure, reducing low-frequency reflections. Comparative Example 3 (lacking pure PU microspheres) lacks these mechanisms, resulting in a 29% decrease in low-frequency sound absorption coefficient. Comparative Example 5 (single-layer structure) exhibits the worst low-frequency sound absorption, at 0.35, demonstrating the importance of a gradient structure for broadband sound absorption. Example 8 exhibits the best average sound absorption coefficient (1-5 kHz) of 0.84, due to its gradient pore size matching different frequency bands. Comparative Example 5, however, exhibits the worst average sound absorption coefficient (1-5 kHz) of 0.58, due to the lack of a layered structure, which results in a sudden change in acoustic impedance and increased reflections. The GQD sensitivity of Example 8 is 8.7% / kPa, the highest, due to the optimization of quantum dot distribution by pre-strain of 0.5%; while in Comparative Example 7, there is no pre-strain and the hysteresis increases by 30%, proving that strain treatment plays a key role in stabilizing the conductive path.
[0054] Environmental aging test: Humidity and heat aging: 85℃ / 85%RH, take out and test once every 24 hours Salt spray test: ASTM B117, 5% NaCl solution, spray volume 1.5 mL / h Table 3 85℃ / 85%RH, 7-day performance retention rate (%) Salt spray test (96h) performance retention rate (%) Example 4 The sound absorption coefficient decreased by 4% and the resistance fluctuation increased by 7%. Peel strength decreased by 8%, no visible corrosion Example 5 The sound absorption coefficient decreased by 3%, and the resistance fluctuation increased by 5%. Peel strength decreased by 7%, no corrosion Example 6 The sound absorption coefficient decreased by 5%, and the resistance fluctuation increased by 9%. Peel strength decreased by 10%, and the edge was slightly oxidized Example 7 The sound absorption coefficient decreased by 4% and the resistance fluctuation increased by 8%. Peel strength decreased by 9%, no corrosion Example 8 The sound absorption coefficient decreased by 2%, and the resistance fluctuation increased by 3%. Peel strength decreased by 5%, no corrosion Example 9 The sound absorption coefficient decreased by 3% and the resistance fluctuation increased by 6%. Peel strength decreased by 7%, no corrosion Example 10 The sound absorption coefficient decreased by 3%, and the resistance fluctuation increased by 5%. Peel strength decreased by 6%, no corrosion Comparative Example 1 The sound absorption coefficient decreased by 12% and the resistance fluctuation increased by 20%. Peel strength decreased by 25%, and surface blistering occurred. Comparative Example 2 The sound absorption coefficient decreased by 15%, and the resistance fluctuation increased by 23%. Peel strength decreased by 30%, CNT oxidation Comparative Example 3 The sound absorption coefficient decreased by 18% and the mechanical strength decreased by 34%. The peel strength decreased by 23%, and the surface was slightly blistering. Comparative Example 4 The sound absorption coefficient decreases by 10%, and the resistance fluctuation increases by 15%. Peel strength decreased by 18%, local corrosion Comparative Example 5 The sound absorption coefficient decreased by 15% and the mechanical strength decreased by 31%. Delamination and cracking, unable to test Comparative Example 6 Sound absorption coefficient decreased by 8%, no sensing function Surface micro-erosion, peel strength decreased by 15% Comparative Example 7 The sound absorption coefficient decreased by 5%, and the resistance hysteresis increased by 39%. The peel strength decreased by 10%, and the GQD partially fell off. As shown in Table 3, in the wet heat aging test, Examples 5-10 achieved performance retention rates exceeding 95%, attributed to the hydrophobicity of the epoxidized soybean oil and the antioxidant properties of the GQDs. However, the large resistance fluctuations in Comparative Example 2 (no graphene) were primarily due to the increased susceptibility of CNTs to oxidation under wet heat. In the salt spray corrosion test, the lignin-based carbon fibers in Example 8 formed an anti-corrosion barrier, reducing the corrosion rate by 50%. However, the absence of a gradient buffer in Comparative Example 5 (single layer) resulted in delamination due to Cl⁻ penetration.
[0055] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.
Claims
1. A lightweight sound-absorbing and silent sponge, characterized in that: The lightweight sound-absorbing and silent cotton has a bionic gradient structure and is divided into three layers. The bottom layer dissipates high-frequency sound waves, the middle layer optimizes mid-frequency resonance, and the upper layer enhances low-frequency sound wave scattering.
2. A method for preparing a lightweight sound-absorbing and silent sponge, characterized in that: The following steps are involved: Step 1: 3 wt.% TEMPO oxidized cellulose nanofibers, 18-20 wt.% PU / carbon nanotube composite microspheres, 35 wt.% aqueous polyurethane emulsion, 1 wt.% sodium alginate, 0.1 wt.% silane coupling agent KH550, and the remainder water were mixed and stirred to form a bottom slurry; Step 2: 5 wt.% of TEMPO oxidized cellulose nanofibers, 15-18 wt.% of PU / graphene composite microspheres, 35 wt.% of aqueous polyurethane emulsion, 0.5 wt.% of xanthan gum, 0.1 wt.% of silane coupling agent KH550, and the remainder of water are mixed and stirred to form a middle layer slurry; Step 3: 7 wt.% TEMPO oxidized cellulose nanofibers, 10-12 wt.% pure PU microspheres, 1-2 wt.% lignin carbon fibers, 1 wt.% epoxidized soybean oil, 35 wt.% aqueous polyurethane emulsion, 0.1 wt.% silane coupling agent KH550, and the remainder water were mixed and stirred to form an upper slurry; Step 4: Pre-cool the bottom of the mold to -30°C and use a three-channel injection system to simultaneously inject three layers into the mold: Bottom slurry injection flow rate: 0.1 mL / s, injection height 1 mm; Middle layer slurry injection flow rate: 0.15 mL / s, injection height 2 mm; Upper slurry injection flow rate: 0.2 mL / s, injection height 1 mm; Step 5: One-way freezing: After injection, let it stand for 1 minute, move the mold to a -50℃ cold table, open the top, and form a longitudinal gradient pore size; Step 6: Freeze drying: drying at -50°C / 10Pa for 48 hours to obtain a three-layer gradient structure material; Step 7: Immerse in a 0.5 wt.% graphene oxide quantum dot ethanol solution and vacuum treat at 0.01 MPa for 2 h; Step 8: Heat to 60 °C, add 0.1 wt.% ascorbic acid, hold for 2 h, and apply 0.5% prestrain to the material; Step 9: Photothermal curing: UV curing after near-infrared treatment; Step 10: Heat press and shape.
3. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: In the step 1, the diameter of the TEMPO oxidized cellulose nanofibers is 20-50 nm, and the particle size of the PU / carbon nanotube composite macromicrospheres is 30-80 μm.
4. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: The preparation method of the PU / carbon nanotube composite macromicrospheres in step 1 is as follows: 20 wt.% of a carboxylated CNT dispersion with a concentration of 1 wt.% is slowly added to a 60 wt.% PU emulsion with a solid content of 30 wt.%, magnetically stirred at 500 rpm for 30 minutes, homogenized at 50 MPa high pressure, 2 wt.% hydroxyethyl cellulose and 18 wt.% deionized water are added and stirred, spray dried to form, and cured in an oven at 80°C for 2 hours to obtain the obtained product.
5. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: In the step 2, the diameter of the TEMPO-oxidized cellulose nanofibers is 20-50 nm, and the particle size of the microspheres in the PU / graphene composite is 15-30 μm.
6. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: The preparation method of the PU / graphene composite mesosphere particles in step 2 is as follows: 50 wt.% polyurethane prepolymer, 30 wt.% acetone and 0.1 wt.% dibutyltin dilaurate are mixed to obtain an oil phase; 15 wt.% GO dispersion and 4.9 wt.% emulsifier are mixed to obtain an aqueous phase; the oil phase and the aqueous phase are mixed at 50°C and emulsified at high shear speed; the mixture is circulated three times at a homogenization pressure of 20 MPa to obtain a W / O emulsion; ethylenediamine is added and reacted at 60°C for 2 hours; acetone is slowly evaporated at 40°C for 6 hours to form dense microspheres, which are then immersed in 1 wt.% ascorbic acid at 60°C for 12 hours to obtain PU / graphene composite mesospheres with a size of 15-30 μm.
7. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: In step 3, the diameter of the TEMPO oxidized cellulose nanofibers is 20-50 nm, the particle size of the pure PU microspheres is 5-10 μm, and the particle size of the lignin carbon fibers is 1-2 μm.
8. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: In step 9, the near-infrared treatment conditions are 808 nm, 1 W / cm2, and 30 s; the UV curing conditions are 365 nm, 600-800 mJ / cm2.
9. The method for preparing a lightweight sound-absorbing and silent sponge according to claim 2, characterized in that: The hot pressing and shaping conditions in step 10 are 0.1 MPa, 60° C., and 5 min.
Citation Information
Cited By
Composite textile sound absorption material based on nanofibers and continuous production equipment
CN120921777A